2020
DOI: 10.3389/fpsyt.2020.00296
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Brain Derived Neurotrophic Factor and Cell Adhesion Molecules as Biomarkers for the Transdiagnostic Symptom Anhedonia in Alcohol Use Disorder and Comorbid Depression

Abstract: Background: Alcohol Use Disorder (AUD) and depressive disorder often co-exist and have a shared heritability. This study aimed to investigate Brain-Derived Neurotrophic Factor (BDNF) and three Cell Adhesion Molecules (CAMs) as transdiagnostic biomarkers in AUD and depression co-morbidity. Methods: In a cross-sectional study, patients with AUD (n=22), AUD and depression (n=19), and healthy controls (n=20) were examined. Depression and anxiety severity were assessed using the Hamilton Depression Rating Scale and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 55 publications
1
6
1
1
Order By: Relevance
“…In contrast, Primary MD patients met more criteria related to anhedonia, loss of concentration and recurrent thoughts of death. Our results are not according to other studies and show that depressive co-morbidity in patients with AUD may thus be characterized by more pronounced levels of anhedonia, as compared to other symptom domains of depression [ 73 ]. Animal and human studies were the focus in the paper of anhedonia as a transdiagnostic symptom.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, Primary MD patients met more criteria related to anhedonia, loss of concentration and recurrent thoughts of death. Our results are not according to other studies and show that depressive co-morbidity in patients with AUD may thus be characterized by more pronounced levels of anhedonia, as compared to other symptom domains of depression [ 73 ]. Animal and human studies were the focus in the paper of anhedonia as a transdiagnostic symptom.…”
Section: Discussioncontrasting
confidence: 99%
“…The DG is also affected by other biological processes that regulate neural structure and function, such as cell adhesion, chemical synaptic transmission, and neuroactive ligand-receptor interaction. Some studies have shown that cell adhesion plays a vital role in depression-related behavior [ 48 50 ]. It is well documented that MDD is linked to excitation inhibition imbalance due to disrupted synaptic transmission [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms were assessed using the 17-item Hamilton Depression Rating Scale (HAMD-17) as derived from the Structured Interview Guide for the Hamilton Depression Rating Scale—Seasonal Affective Disorder version (SIGH-SAD) [ 29 , 30 ]. The other transdiagnostic symptom domains were assessed using Russian translations of commonly applied self-report questionnaires [ 31 ]. All self-report questionnaires were common Russian translations of the originals (verified by back translation into English).…”
Section: Methodsmentioning
confidence: 99%
“…The BDHI is a self-reporting questionnaire containing 75 points to estimate seven aspects of hostility: assault, indirect hostility, irritability, negativism, resentment, suspicion, and verbal hostility. Details on the other scales have been described previously [ 31 ].…”
Section: Methodsmentioning
confidence: 99%